Legal Protection of the Civil Rights of Local Miners in Land Acquisition through Corporate Tali Asih Practices - Titip Suroso; Hijrah lahaling; Nur Insani (Judge : Jurnal Hukum, 2025)
Mining activities in Pohuwato Regency generate economic benefits while simultaneously giving rise to legal issues, particularly concerning land acquisition carried out through tali asih mechanisms. This practice often places local mining communities in a legally vulnerable position due to unequal power relations with mining companies and the absence of clear legal regulation. This study aims to analyze the legal standing of local mining communities in land acquisition practices conducted through tali asih mechanisms and to formulate forms of civil law protection that are fair, proportional, and grounded in social justice. This research employs a normative–empirical legal method with statutory, conceptual, and sociological approaches. Data were obtained through library research on legal regulations and doctrines, as well as empirical data collected through interviews and field observations. The findings indicate that tali asih practices have not fully complied with the principles of freedom of contract, good faith, and equality of the parties, resulting in the protection of the civil rights of local mining communities being largely formal rather than substantive. Furthermore, normative gaps and the weak role of the state in providing preventive protection exacerbate the legal vulnerability of affected communities. This study concludes that strengthening regulatory frameworks and adopting a legal protection approach oriented toward social justice are necessary to ensure that mining-related land acquisition not only provides legal certainty but also guarantees the protection of rights and the sustainability of the livelihoods of local mining communities.